EVALUATION OF THE POLICY OF ELECTRONIC MANAGEMENT OF STATE PROPERTY IN UNIVERSITY OF SEBELAS MARET, SURAKARTA - Harisudin Harisudin; Sudarmo Sudarmo; Rino Ardhian Nugroho (Faculty of Law, Universitas Sebelas Maret, 2017)
This article analyzes the evaluation of the policy of management of State Goods Electronically in Sebelas Maret University of Surakarta. The scope of the Management of the State Property includes : Planning, procurement up to asset management obtained from the procurement (State Property). This is in line with government efforts to improve public services with e-government development electronic base that is used in the case of planning that is making RAB (Budget Plan) in the form of HPS (Own Price Estimated), TOR (Term of Reference) or determination of IKU (Unit Performance Indicator), IKA (Budget Performance Indicator) or MAK (activity budget item). In the process of procurement using e-procurement system also in the management of asset/BMN procurement result using the Application System of SIMAK BMN. Evaluation of the Policy done by looking at the 4 elements as follows:1) To measure the effects Based on the research methodology used; 2) Effects Emphasize on an outcomes of Efficiency, honesty, morals attached to rules or standards; 3) Comparation between the effects and goals emphasizes on the use of clear criteria In assessing how a policy has been properly implemented, 4) Giving contribution to make future decision-making and future policy improvements as the social purpose of the evaluation.